A tutoria nos cursos de licenciatura a distância : saberes docentes e a formação continuada - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The progress of digital media as well as Brazilian educational legislation, has been increasing the offer of College Education, especially in teacher training courses. However, this methodology that facilitates the democratization of teaching through the internalization of courses and flexibility in study schedules, promotes little research in support of its pedagogical proposals and the subjects involved in the teaching and learning process. One of those involved, which is generating increasing discussions, especially in relation to their role, are tutors professors, a justifiable fact, due to the lack of a homogeneous standardization that, perhaps, could valorize the profession. We understand that this professional is responsible for the processes of mediation and pedagogical practices, so he is in fact a professor, but should use different teachers' knowledge than those employed in face-to-face courses. Teaching knowledge is acquired throughout the school life, but due to the historical educational moment, the tutors professors come from an education, predominant, in the face-to-face modality. Thus, they face the lack of training in undergraduate courses. In this sense, a permanent process of training of tutors professors is fundamental, since it will enable the formation of teacher knowledge that will directly reflect on the pedagogical practices developed in the teaching process in the online courses. In this sense, we question: what characterizes the pedagogical training for acting as a tutor professor in the degree courses offered by the Center for Teaching and Learning in Network of the State University of Goiás? In order to answer this question, we aimed to investigate the trajectory of continuing education of tutors who work in Online Education at the University through a qualitative-quantitative approach. We carried out the study of the Political Educational Projects of the Courses to understand the role of tutors professors, through documentary analysis, besides investigating the processes of continuing education offered at the Institution. In the following stage, a questionnaire was applied to the 27 tutors professors who work in the university. The responses were analyzed using the content analysis methodology. We note that the institution considers that the tutors professors are responsible for the pedagogical practices developed in the courses. Thus, a blog was proposed as a last step, which will allow the collective construction of knowledge about acting in online courses, in a permanent process of continuing education, since the whole internet is a rich space of collaboration and knowledge building. We conclude that it is fundamental that the Institution of Education invest in continuing education with the focus on the pedagogical formation of tutors professors. So that the courses are not oriented by technological determinism, but by a pedagogical proposal that attends the interests of the students in consonance with the challenges of sustainability and democratization of the scientific knowledge of the contemporary society. For, with the professionals trained to act in the virtual context will we be able to break with the barriers of Distance Education and materialize Online Education.
Keywords: Formação de tutores; Mídias digitais; Educação online; Mediação pedagógica; Tutors training; Digital media; Online education; Pedagogical mediation; EDUCACAO::ENSINO-APRENDIZAGEM